THE ROLE OF PARALINGUISTIC UNITS IN SPEECH (ON THE MATERIALS OF ENGLISH AND UZBEK LANGUAGES) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The current article focuses on paralinguistic units of English and Uzbek languages, their functions and purposes. Examples from literature of both languages are given as evidence, and some ideas from other valuable sources related to the topic are also discussed and analyzed.